2012
DOI: 10.1021/np200959j
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctionalized Amphilectane Diterpenes from the Sponge Stylissa cf. massa

Abstract: Two new amphilectane-type diterpenes, 8-isocyanato-15-formamidoamphilect-11(20)-ene (1) and 8-isothiocyanato-15-formamidoamphilect-11(20)-ene (2), along with two known derivatives, 8-isocyano-15-formamidoamphilect-11(20)-ene (3) and 7-formamidoamphilect-11(20),15-diene (4), were isolated from the sponge Stylissa cf. massa. Diterpenes bearing two different isonitrile-related functionalities, as in 1-3, are rare. The coexistence of these compounds, all of which possess the identical carbon skeleton, in the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…clvii In total, 9 reports have ascribed varying levels of anti-malarial activity–from weak to single-digit nanomolar–for isonitrile containing natural products and synthetic variants, clearly establishing the ICTs as intriguing antimalarial lead structures. xxx,cxliii,clviii,clix,clx,clxi,clxii , A promising aspect of this collection of data is that several independent studies observed essentially equipotent activity between common chloroquine-sensitive (including D6 and HB3) and drug-resistant/ drug-insensitive (including W2 and Dd2) strains of P. falciparum parasites.…”
Section: Biological Activitymentioning
confidence: 98%
See 1 more Smart Citation
“…clvii In total, 9 reports have ascribed varying levels of anti-malarial activity–from weak to single-digit nanomolar–for isonitrile containing natural products and synthetic variants, clearly establishing the ICTs as intriguing antimalarial lead structures. xxx,cxliii,clviii,clix,clx,clxi,clxii , A promising aspect of this collection of data is that several independent studies observed essentially equipotent activity between common chloroquine-sensitive (including D6 and HB3) and drug-resistant/ drug-insensitive (including W2 and Dd2) strains of P. falciparum parasites.…”
Section: Biological Activitymentioning
confidence: 98%
“…xxvi The variety of amphilectane structures has also grown, as shown in Figure 4B. xx,xxvii,xxviii,xxix,xxx Of particular interest are the methylamine and formamide, 77–78 , variants of the isoneoamphilectane scaffold, which were obtained from a Svenzea flava sponge and shown to display moderate antitubercular activity (MICs between 6 and 32 µg/mL against a M. tuberculosis H 37 RV). xxxi Also quite notable was a significant reassignment effort of the absolute and relative stereochemistry of several previously assigned xxxii compounds through a combination of X-ray and Mosher ester analysis.…”
Section: Recent Progress In Isolationmentioning
confidence: 99%
“…), 705 a potent antimalarial, has been achieved, 706 while the isolation of two new formamido-amphilectane diterpenes 829 and 830 from a Thai Stylissa massa (Koh-Tao, Surat-Thani Province) have been reported. 707 Jaspiferin A 831 was isolated from Jaspis stellifera (Guangdong, South China Sea) along with an oxidative degradation product jaspiferin B 832. 708 Chromodorolide D 833, a heavily rearranged spongian diterpene, was reported along with 834 from an unidentied sponge (Cape Manza, Okinawa).…”
Section: Spongesmentioning
confidence: 99%
“…Examination of the sponge Stylissa cf. massa, collected also in Koh-Tao (Thailand) by Chanthathamrongsiri in 2012 revealed two C-5 derivatives of Amp2 , 8-isocyanato-15-formamidoamphilect-11(20)-ene ( Amp8 ) and 8-isothiocyanato-15-formamidoamphilect-11(20)-ene ( Amp9 ) [ 123 ].…”
Section: Marine Isonitriles and Related Compoundsmentioning
confidence: 99%
“…In agreement with these findings are the results of Chanthathamrongsiri et al who proved the C-8 isonitrile Amp2 to have a tenfold higher antiplasmodial activity than the isocyanate ( Amp8 ) and the isothiocyanate Amp9 . The C-7-formamide Amp17 was inactive [ 123 ].…”
Section: Biological Activitymentioning
confidence: 99%